The Application of Animal Biotechnology in the Cattle Industry - Afifi Syukrina, Rudy; Eqa Fahiszah, Madian; Mohammad Amirul Amizan, Baidi; Mohammad Nazri, Ronard; Nur Alia Athirah, Mohd Hanapiah; Hung Hui, Chung (UNIMAS Publisher, 2025)
An animal is in a good state of wellbeing if it is free from pain, fear, and distress and is able to exhibit its natural behaviour in a safe environment. The scientific methods for evaluating animal well-being have advanced quickly in recent years, and many of these methods can be used to evaluate genetically-modified (GM) or biotech-treated animals. Measures of physiology, behaviour, anatomy, immunological function, pathological change, growth, reproduction, and longevity should be used to evaluate each modified strain or treated animal in comparison to unmodified or untreated animals. Any elevated levels of pain, fear, or distress should be exposed via many indicators. These indices reveal how dismal welfare really is, but other research can reveal how much improvement is possible. These ideas on animal welfare are not just applicable to cattle; they may be applied to any animal that has any kind of relationship with a human being, such as an agricultural animal, a companion animal, an animal employed in a circus or zoo, or an animal that is used for scientific research.